İmmünoloji polikliniğine sık enfeksiyon nedeniyle başvuran hastaların profili - (:unkn) unknown (My University, 2014)
Amaç: Sık enfeksiyon geçirme öyküsü ile kliniğimiz immünoloji po- likliniğine başvuran ve birincil immün yetersizlik için uyarıcı bulgu- ları olan çocuklar arasında birincil immün yetersizlik (BİY) oranının belirlenmesini amaçladık. Gereç ve Yöntemler: Sık enfeksiyon geçirme yakınmasıyla çocuk im- münoloji polikliniğimize yönlendirilen çocuklar arasından BİY için uyarıcı beliritileri olan 1-18 yaş arasındaki 232 çocuğun dosyası seçi- lerek geriye dönük olarak değerlendirildi. Bulgular: Olguların %36sı (n=84) kız, %64ü (n=148) erkekti. %72,4ünde (n=164) BİY saptandı. En sık tanı %26,3 (n=61) ile selektif IgA eksikliği idi. Birincil immün yetersizlik dışında en çok saptanan hastalıklar ise %34,4 (n=22) reaktif hava yolu hastalığı ve/veya atopi, %12,3 (n=8) adenoid vejetasyon, %6,3 (n=4) kronik hastalık ve %4,6 (n=3) periyodik ateş, aftöz stomatit, adenopati idi. Olguların çoğun- luğu %90,5 (n=210) yineleyen üst solunum yolu enfeksiyonu yakın- masıyla başvurdu. Bronşektazisi olan tüm olgularda BİY saptandı. Alt solunum yolu enfeksiyonu geçiren, enfeksiyon nedeniyle hastaneye yatan ve ciddi enfeksiyon öyküsü olanlarda, olmayanlara göre de- ğişken immün yetersizlik ve Bruton agamaglobulinemisi (XLA) tanı oranları anlamlı oranda yüksek bulundu (sırasıyla p<0,05 ve p<0,01). Ağır kombine immün yetersizlik ve hiper IgM tanılı hastalarda bü- yüme gelişme geriliği diğer olgulara göre anlamlı olarak yüksek sap- tandı (p<0,01). Yaş grupları arasında BİY oranlarında fark bulunmadı, ancak başvuru yaşı arttıkça XLA alma oranları da artmaktaydı ve bu XLA olgularının geç tanı aldığının bir göstergesi olarak kabul edildi. Çıkarımlar: Sık enfeksiyon geçiren olgular, BİY uyarıcı belirtilerine göre seçildiğinde tanı oranının oldukça yüksek (%72,4) olduğu sap- tanmıştır. (Türk Ped Arş 2014; 49: 210-6)

Aim: We aimed to determine the rate of primary immune deficiency (PID) among children presenting to our immunology outpatient cli- nic with a history of frequent infections and with warning signs of primary immune deficiency. Material and Methods: The files of 232 children aged between 1 and 18 years with warning signs of primary immune deficiency who were referred to our pediatric immunology outpatient clinic with a compla- int of frequent infections were selected and evaluated retrospectively. Results: Thirty-six percent of the subjects were female (n=84) and 64% were male (n=148). PID was found in 72.4% (n=164). The most common diagnosis was selective IgA deficiency (26.3%, n=61). The most common diseases other than primary immune deficiency inc- luded reactive airway disease and/or atopy (34.4%, n=22), adenoid vegetation (12.3%, n=8), chronic disease (6.3%, n=4) and periodic fe- ver, aphtous stomatitis and adenopathy (4.6%, n=3). The majortiy of the subjects (90.5%, n=210) presented with a complaint of recurrent upper respiratory tract infection. PID was found in all subjects who had bronchiectasis. The rates of the diagnoses of variable immune deficiency and Bruton agammaglubulinemia (XLA) were found to be significantly higher in the subjects who had lower respiratory tract infection, who were hospitalized because of infection and who had a history of severe infection compared to the subjects who did not have these properties (p<0.05 and p<0.01, respectively). Growth and developmental failure was found with a significantly higher rate in the patients who had a diagnosis of severe combined immune de- ficiency or hyper IgM compared to the other subjects (p<0.01). No difference was found in the rates of PID between the age groups, but the diagnosis of XLA increased as the age of presentation increased and this was considered an indicator which showed that patients with XLA were being diagnosed in a late period. Conclusions: It was found that the rate of diagnosis was considerably high (72.4%), when the subjects who had frequent infections were selected by the warning signs of PID. (Türk Ped Arş 2014; 49: 210-6)
Profile of the patients who present to immunology outpatient clinics because of frequent infections
Keywords: Hematoloji; Enfeksiyon Hastalıkları; Pediatri